IMPLEMENTASI METODE GARIS LURUS & METODE JUMLAH PRODUKSI PADA SISTEM INFORMASI AKUNTANSI ASET TETAP PADA PNS GRUP BATANG - miftah miftah; Diah Ayu Pertiwi; Muhamad Sidik (Universitas Sains dan Teknologi Komputer, 2020)
Fixed assets are one of the elements in the financial statements, the value of fixed assets in companies tends to be in large amounts. Investments in fixed assets by the company are intended to support the company's business activities. Every transaction that affects changes in fixed assets must be managed in order to produce information in the form of financial statements. Improper handling of fixed assets will have an impact on finances and improper handling of fixed assets because they still practice a manual system that allows for various problems in financial reporting. The research objective is to build an accounting information system for depreciation of the company's fixed assets which produces output in the form of fixed asset information that can facilitate management in making business decisions. The research method uses research and development methods, using six steps from ten steps of the R&D model. The system development model uses the Prototype model approach to produce products according to user needs. This research produces a fixed asset management information system product that is able to assist in handling fixed asset management transactions and the information system is capable of producing fixed asset accounting information quickly. Keywords: Accounting Information Systems, Fixed Assets, Straight-Line Method and Total Production